Systemic inflammation and risk stratification in pheochromocytoma: Insights from PASS components, TNM stage, and the tumor immune microenvironment - Ümit Çavdar; Tuğçe Tekinaslan; Özlem Eren; Emine Özlem Gür; Serkan Karaıslı; Mehmet Haciyanli; Selda Gücek Haciyanli; Aslı Kahraman; Mehmet Sercan Ertürk; Barış Önder Pamuk; Serkan Yener (Eurasian Journal of Medicine and Oncology, 2026)
Introduction: The Pheochromocytoma of the Adrenal Gland Scaled Score (PASS) and Tumor–Node–Metastasis (TNM) staging capture histopathological and anatomical risk features in adrenal pheochromocytoma, but do not incorporate systemic inflammation. Objectives: To investigate the associations of preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) with individual PASS components and American Joint Committee on Cancer TNM stage in adrenal pheochromocytoma. Methods: We retrospectively screened 62 patients; after predefined exclusions, 55 patients with adrenal pheochromocytoma were included. Clinical characteristics, tumor size, urinary metanephrine and normetanephrine levels, PASS components, TNM stage, and preoperative blood counts were recorded. Associations of NLR and PLR with PASS components were assessed using univariate logistic regression, with Benjamini–Hochberg correction across the 12 component-level analyses. NLR and PLR were also compared between Stage I/II and Stage III/IV disease. Results: After Benjamini–Hochberg correction, associations of NLR with vascular invasion and high cellularity were attenuated, whereas those with capsular invasion, large nests or diffuse growth, tumor necrosis, atypical mitosis, and mitotic activity > 3/10 high-power fields remained significant. NLR was higher in Stage III/IV than Stage I/II disease (median: 3.85; range: 2.17–6.73 vs. median: 2.59; range: 1.52–5.48, p = 0.019). PLR was associated with PASS ≥ 6 in the unadjusted analysis but not with individual PASS components and did not differ by stage. Conclusion: Higher preoperative NLR was associated with selected PASS components and Stage III/IV disease in adrenal pheochromocytoma. These exploratory findings require validation in larger multicenter cohorts and should not be interpreted as evidence of independent prognostic value.